Geometric comb waveforms for reverberation suppression - Cox, H.; Hung Lai (Proceedings of 1994 28th Asilomar Conference on Signals, Systems and Computers, 1994)
The major problem for sonar systems operating in shallow water is reverberation from the ocean bottom. A new class of waveforms is described which combines high range resolution with excellent Doppler properties for detecting moving targets in stationary reverberation. The waveforms consist of multiple simultaneously transmitted CW tone pulses. The tones are non-uniformly spaced in frequency to break up range ambiguities. A special subclass is the geometric comb in which the frequency spacing between the adjacent components follows a geometric progression. Analytic approximations can be used to obtain the important properties of this class, resulting in a practical design methodology. The resulting waveforms have excellent Doppler properties and an unambiguous high resolution range estimation capability. Techniques for reducing the peak-to-average power ratio are discussed.< >